Miridiba hani Gao, a new species from Hainan, China (Coleoptera: Scarabaeidae: Melolonthinae: Rhizotrogini), with a new combination from Vietnam - Gao, Chuan-Bu; Bai, Ming; Fang, Hong; Li, Jun (Zootaxa, 2021)
A new species of the genus Miridiba Reitter, 1902 from Hainan Island of China is described and illustrated: Miridiba hani Gao, new species. A key to the species of the genus Miridiba known in Hainan Island is provided. A new combination is proposed: Miridiba longiuscula (Moser, 1909), new combination.